Predicting pathological response of esophageal cancer to neoadjuvant chemotherapy: the implications of metabolic nodal response for personalised therapy - Findlay, J; Bradley, K; Mun Wang, L; Franklin, J; Teoh, E; Gleeson, F; Maynard, N; Gilies, R; Middleton, M (Society of Nuclear Medicine, 2016)
INTRODUCTION Only a minority of esophageal cancers demonstrates a pathological tumor response (pTR) to neoadjuvant chemotherapy (NAC). 18F-fluorodeoxyglucose (FDG) positron emission tomography-computed tomography (PET-CT) is often used for restaging after NAC and to assess response. Increasingly, it is used during therapy to identify unresponsive tumors and predict pTR , using avidity of the primary tumor alone. However, definitions of such metabolic tumor response (mTR) vary. We aimed to comprehensively re-evaluate metabolic response assessment using accepted parameters, as well as novel concepts of metabolic nodal stage (mN) and nodal response (mNR). PATIENTS AND METHODS This was a single-center retrospective UK cohort study. All patients with esophageal cancer staged before NAC with PET-CT and after with CT or PET-CT and undergoing resection from 2006-2014 were identified. pTR was defined as Mandard tumor regression grade 1-3; imaging parameters included metrics of tumor avidity (standardized uptake value [SUV]max/mean/peak), composites of avidity and volume (including metabolic tumor volume), nodal SUVmax, and our new concepts of mN stage and mNR. RESULTS Eighty-two (27.2%) of 301 patients demonstrated pTR. No pre-NAC PET parameters predicted pTR. In 220 patients re-staged by PET-CT, The optimal tumor ΔSUVmax threshold was a 77.8% reduction. This was as sensitive as the current PET Response Criteria in Solid Tumors (PERCIST) 30% reduction, but more specific with a higher negative predictive value (p<0.001). ΔSUVmax and Δlength independently predicted pTR, and composite avidity/spatial metrics outperformed avidity alone. Whilst both mTR and mNR were associated with pTR, in 82 patients with FDG-avid nodes before NAC we observed mNR in 10 (12.2%) not demonstrating mTR. CONCLUSION Current definitions of metabolic response are suboptimal and too simplistic. Composite avidity/volume measures improve prediction. mNR may further improve response assessment, by specifically assessing metastatic tumor sub-populations, likely responsible for disease relapse, and should be urgently assessed when considering aborting therapy on the basis of mTR alone.